Electrically conductive porous Ti3C2Tx MXene-polymer composites from high internal phase emulsions (HIPEs). (22nd September 2022) - Cao, Huaixuan; Wang, Yifei; Sarmah, Anubhav; Liu, Kai-Wei; Tan, Zeyi; Arole, Kailash Dhondiram; Lutkenhaus, Jodie L; Radovic, Miladin; Green, Micah J; Pentzer, Emily B
Abstract: Porous MXene-polymer composites have gained attention due to their low density, large surface area, and high electrical conductivity, which can be used in applications such as electromagnetic interference shielding, sensing, energy storage, and catalysis. High internal phase emulsions (HIPEs) can be used to template the synthesis of porous polymer structures, and when solid particles are used as the interfacial agent, composites with pores lined with the particles can be realized. Here, we report a simple and scalable method to prepare conductive porous MXene/polyacrylamide structures via polymerization of the continuous phase in oil/water HIPEs. The HIPEs are stabilized by salt flocculated Ti3 C2 T x nanosheets, without the use of a co-surfactant. After polymerization, the polyHIPE structure consists of porous polymer struts and pores lined with Ti3 C2 T x nanosheets, as confirmed by scanning electron microscopy, energy dispersive x-ray spectroscopy, and x-ray photoelectron spectroscopy. The pore size can be tuned by varying the Ti3 C2 T x concentration, and the interconnected Ti3 C2 T x network allows for electrical percolation at low Ti3 C2 T x loading; further, the electrical conductivity is stable for months indicating that in these composites, the nanosheets are stable to oxidation at ambient conditions. The polyHIPEs also exhibit rapid radio frequency heating at low power (10 °C s −1 at 1 W). This work demonstrates a simple approach to accessing electrically conductive porous MXene/polymer composites with tunable pore morphology and good oxidation stability of the nanosheets.